2021
DOI: 10.1021/acssuschemeng.1c04334
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Lignin-graft-poly(ethylene brassylate): a Biomass-Based Polyester with High Mechanical Properties

Abstract: Lignin is an important biopolymer that can be used as a raw material to produce functional polymers due to its abundance, low price, sustainability, and high concentration of aromaticity. However, lignin modification is not well understood or characterized, limiting its potential as a new sustainable raw material. The biopolymer lignin can be integrated with aliphatic polyesters to produce new biomass-based biodegradable polymers. Among various aliphatic polyesters, poly­(ethylene brassylate) (PEB) is a relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 55 publications
0
23
1
Order By: Relevance
“…15 Furthermore, the results demonstrated that the mechanical properties have been enhanced after introducing lignin into the PU prepolymer. 16–18 The main reason is that lignin can act as hard segments and hard crosslinking points, leading to improved mechanical stiffness. Therefore, the mechanical properties of PU-based gels would be greatly enhanced via introducing crosslinking points.…”
Section: Introductionmentioning
confidence: 99%
“…15 Furthermore, the results demonstrated that the mechanical properties have been enhanced after introducing lignin into the PU prepolymer. 16–18 The main reason is that lignin can act as hard segments and hard crosslinking points, leading to improved mechanical stiffness. Therefore, the mechanical properties of PU-based gels would be greatly enhanced via introducing crosslinking points.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the amount of reacted PEG in modified lignin-graft-PEG, the number of reactive sites (−COOH) on modified lignin was calculated based on 1 H NMR spectra (Figure b). The number of hydroxyl groups on lignin was reported previously. ,, According to the previously reported data, one gram of lignin possesses 4.48 mmol of hydroxyl groups. Thus, the number of reactive sites (−COOH) of uncapped lignin with 0% of acetic acid (UCL, entry 4 in Table S1) is 4.48 mmol per one gram of lignin.…”
Section: Resultsmentioning
confidence: 79%
“… a Acetic acid was used as a capping agent. b X CL- Y P Z , where X = mole % of the capping agent; Y = molecular weight of PEG; Z = mass ratio of modified lignin with PEG (6CL-2P13 (entry 13 in Table ) indicates a copolymer of modified lignin which capped 6 mol % and PEG of 2k g/mol with a 1:3 (lignin: PEG) weight ratio). c mmol of the reactive site (carboxylic acid) per one gram of lignin was determined by 1 H NMR of modified lignin (Figure b). There is 4.48 mmol of the hydroxyl groups in one gram of lignin. ,, d mmol of added PEG per one gram of lignin. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations